Strategy of Allocating Special Autonomy Funds (Dana Otsus) as an Effort to Strengthen the NKRI in Facing Threats in Papua - Rusli, Fauzi; Sutanto, Rudy; Halkis, Mhd. (Formosa Journal of Science and Technology, 2024)
This study examines the allocation strategy of Special Autonomy Funds (Dana Otsus) in Papua as an effort to strengthen Papua's integration within the framework of the Unitary State of the Republic of Indonesia (NKRI) amidst challenges of separatism and social injustice. A qualitative approach was adopted, involving an in-depth literature review of policies, government reports, and academic resources. The study aims to analyze the effectiveness of Dana Otsus management in addressing development disparities, enhancing welfare, and alleviating social tensions in Papua. The findings indicate that major challenges in managing Dana Otsus include misalignment of development priorities with local needs, weak transparency, and limited human resource capacity. While Dana Otsus has had a positive impact, particularly in the education and healthcare sectors, its implementation remains suboptimal. The study concludes that improving coordination between central and local governments, ensuring transparency, and increasing local community participation are crucial. An inclusive and locally responsive allocation strategy is recommended to optimize the role of Dana Otsus in promoting equitable development and strengthening NKRI.